MODEL KOMUNIKASI DAN PEMBENTUKAN KONSEP DIRI (Studi Deskriptif Kualitatif mengenai Model Komunikasi Pembimbing dalam Proses Pembentukan Konsep Diri pada Klien di Balai Rehabilitasi Sosial âKARTINIâ Tawangmangu) - Jati, Tawangsari Anindya; Hastasari, Chatia; Ruthnia, Firdastin (KOMUNITAS, 2013)
The phenomenon of children on the street is increasingly widespread. This due to the fact that existence is very easy to find particulary in the city center or street even almost all them are disturbing the society, the naughty child and the children on the street tend to live freely with singing on the street and so on. Therefore it needs to establish aÂ  positiveÂ  self conceptÂ  for naughty child and childrenÂ  onÂ  the street. The objective of the research is to determine the comunication model and to classify effective communication model used by conselors in the process of self concept establishment in the client. This research belongs to qualitative descriptive study, data collection techniques usedÂ  observationÂ  andÂ  interview.Â  TheÂ  resultsÂ  ofÂ  this researchÂ  isÂ  theÂ  processÂ  of establishing aÂ  positive self-conceptÂ  onÂ  theÂ  clientÂ  inÂ  socialÂ  rehabilitation centers âKARTINIâ Tawangmangu through three stages of social rehabilitation services consists of some guidance such as the guidance of physical, mental, social skill andÂ  character.Â  TheÂ  guidanceÂ  usesÂ  twoÂ  communicationÂ  models.Â  TheÂ  first communication model effective to estabilish a positive self concept in client with the problems such as ropping out of school, hanging out and so on. Mean while the second communication model effective to clientwhich specific problems such as broken home, drunk, sing on the street and so on.